Transfusion reactions and cognitive aids. Issue 2 (April 2019) - Clebone, Anna
Abstract : Purpose of review: Although the overall safety of blood transfusion is high, adverse events do still occur. Much research on transfusion reactions was done in nonperioperative patients. Fortunately, important contributions to the perioperative literature have been made in the last several years, specifically in the areas of transfusion-associated circulatory overload and transfusion-related acute lung injury (TRALI). Recent findings: An unfavorable reaction occurs in as many as 1% of transfusions overall, although the risk of death with each unit given is between 0.002 and 0.0005%. Specific, modifiable factors exist, however, of which the anesthesiologist should be aware. A 2017 article by Clifford et al. is the first to examine risk factors and outcomes for transfusion-associated circulatory overload in a high-risk noncardiac surgery population undergoing anesthesia and surgery. In recent years, limiting plasma donors to males only resulted in an approximately 50% decrease in TRALI. Summary: The current article explores new research on the topics of transfusion-associated circulatory overload and transfusion-related lung injury.